2013
DOI: 10.14207/ejsd.2013.v2n4p263
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Remittances on Poverty among Rural Households in Nigeria

Abstract: Poverty in Nigeria is more prevalent in therural sector due to dwindling and inequitabledistribution of real income. Remittances (money and goods sent by migrants to relativesback home) can be poverty reducing. However,the extent to which remittances affectpoverty and income inequality has not been adequately documented inNigeria.This paperuses a large, nationally-representative household survey to analyse the impact of domesticremittances (from Nigeria) and foreign remittances (from African and other countrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 13 publications
3
26
0
Order By: Relevance
“…In 2001, for example, 37% of urban households had remitted cash in the previous year, the same proportion as in 1991. 67 However, given Windhoek's dramatic growth during the 1990s, this means that the absolute number of rural households receiv- households in formal and informal settlements in Windhoek. 72 Again, there was a strong migration connection with 49% of households consisting exclusively of migrants, 40%…”
Section: Case Study Two Reciprocal Urban Rural Remitting: Namibiamentioning
confidence: 99%
“…In 2001, for example, 37% of urban households had remitted cash in the previous year, the same proportion as in 1991. 67 However, given Windhoek's dramatic growth during the 1990s, this means that the absolute number of rural households receiv- households in formal and informal settlements in Windhoek. 72 Again, there was a strong migration connection with 49% of households consisting exclusively of migrants, 40%…”
Section: Case Study Two Reciprocal Urban Rural Remitting: Namibiamentioning
confidence: 99%
“…In another study on the effects of remittances on poverty on rural households in Nigeria, Olowa, et al (2013) used a large nationally-representative household survey to analyze the impact of domestic remittances (from Nigeria) and foreign remittances (from African and other countries) on poverty in rural Nigeria. The data for the study was the National Living Standard Survey (N.LSS) collected by the National Bureau of Statistics (NBS), The data extracted for the study (which invariably can be regarded as the independent variables) included socio-economic characteristic, expenditure, household income, Domestic Remittances (DRs) and foreign Remittances (RFs).…”
Section: Empirical Literature Reviewmentioning
confidence: 99%
“…The Central Bank of Nigeria (CBN) officially started recording remittance transfers in the nation's current account balance of payment account books in 2002 (Olowa, Awoyemi,Shittu and Olowa, 2013). As a result of banking reforms of 2004-2006, the remittance figures rose dramatically from a modest $2.26 billion in 2004 to $I4.47 billion in 2005 and $19.20 billion in 2008.…”
Section: Introductionmentioning
confidence: 99%
“…The study chose the second method whereby remittances are treated as exogenous transfers because it provides a simplified picture of the remittances" impact on poverty. This method of research was also used by Adams (2004Adams ( , 2006, Olowa et al (2013) and Sobrevinas (2013). Thus, following the empirical studies on direct impact remittances have on poverty by Adams and Page (2003), Ravallion (1997), Gupta et al (2009) and Gaaliche and Zanyati (2015) the study extends the basic Ravillion and Chen growth-poverty model to include GDP per capita income, Gini coefficient, remittances, literacy rate, unemployment and inflation.…”
Section: Theoretical Modelmentioning
confidence: 99%
“…The study, like Pindiriri et al 2016) has chosen Consumption per Capita as a measure of poverty because it has the advantage of being easy to construct and understand. More so household consumption was chosen because previous studies such as that of Adams (2006) and Olowa et al (2013) showed that households averagely reported smaller income than consumption. The households are more willing to report consumption than their income.…”
Section: Household Per Capita Consumptionmentioning
confidence: 99%